Disparities in Telehealth Utilization Within Pediatric Gastroenterology: One Academic Center's Experience. Issue 2 (August 2021) - Puthenpura, Vidya; Du, Nan; Hauptman, Leora; Porto, Anthony F.
ABSTRACT: Objectives: While the use of telemedicine has accelerated significantly with the recent pandemic, it has also magnified disparities in access to telemedicine. This study aims to look at telemedicine utilization patterns within a large pediatric gastroenterology practice. Methods: A retrospective study of ambulatory care visits within Yale-New Haven Hospital's pediatric gastroenterology practice during the peak expansion of the telemedicine program was conducted. Zip code−level socioeconomic data were obtained using the Distressed Communities Index. A multivariate logistic regression to evaluate disparities between the use of video versus telephone visits was computed, and unadjusted and adjusted odds ratios with 95% confidence intervals (CIs) were obtained. Results: A total of 1273 clinic visits were included in analysis. The majority of the patients listed English as their preferred language, had private insurance, and identified as non-Hispanic White. When adjusting for co-variates, having public insurance/Medicaid was associated with decreased odds of having video over telephone visits (adjusted odds ratio [aOR] 0.60; 95% CI 0.44–0.80). Those whose primary language was not English continued to have a statistically significant decreased odds of using video visits (Spanish aOR 0.24; 95% CI 0.13–0.44; other aOR 0.29; 95% CI 0.12–0.72). Within the adjusted multivariate logistic regression, race/ethnicity and SES were, however, no longer found to have a statistically significant decreased odds of video visits. Conclusions: The accelerated implementation of telemedicine within pediatric gastroenterology has given rise to disparities in its use. Further studies are needed to understand these disparities and develop interventions to lessen this gap in usage. Abstract : Supplemental Digital Content is available in the text